Desain Sensor Serat Optik Sederhana untuk Mengukur Konsentrasi Larutan Gula dan Garam Berbasis Pemantulan dengan Menggunakan Konfigurasi Jarak Cermin-Fiber Optik Tetap - Arrini Nurul M; Ahmad Marzuki; Mohtar Yunianto (Department of Physics, Sebelas Maret University, 2016)
A simple method to measure a solution refractive index using fixed mirror refractive optical fiber sensor has been investigated. The solution used are sugar and salt solution, with concentration varies from 1M to 5M. The diameter of polymer optical fiber used is 0.5 mm and light source used is LED (λ=676 nm). The sensor work based on light intensity modulation, sub jected to mechanical structure change of the fiber due to an applied force. The result showed that the concentration of sugar and salt linearly are related with their refractive indeces (R2=0,95006) and (R2=0,99858).